Periodisitas Tanaman Pekarangan Sebagai Database dalam Pengembangan Wisata Berbasis Konservasi Lingkungan di Desa Sajang, Kecamatan Sembalun, Lombok Timur - Rosalina Edy Swandayani (Fakultas MIPA UNM, 2020)
Abstract. The purpose of this study was to determine the periodicity of fruit and vegetable and ornamental plants which can be used as a database in environmental conservation-based tourism development (agro-tourism) in Sajang Village. The periodicity of natural resource utilization aims to determine the rhythm of plant growth, which is indicated by the presence of fruit and flowers as a sign of plants in their reproductive period (Zakiah et al., 2014). The utilization periodicity is carried out by interviewing the owner of the yard to find out the harvest cycle of the yard plants. This research is a descriptive exploratory research. The observations were made deliberately on 105 yards. Based on the research, the data were analyzed qualitatively, presented in the form of diagrams and descriptions and the results obtained were fruit and vegetable plants in Sajang Village of 52% or 46 types of fruiting plants once a year, 35 types or 39% of the plants bearing fruit once every three months, 6% of crops or five types of crops bear fruit every four months and 5% or a total of four crops harvest and bear fruit every two years. Ornamental plants generally flower during the rainy season, namely in November-May as many as 97 types of plants or 71%, and as many as 29% or 40 types of plants there are ornamental plants that flower throughout the year.Keywords: periodicity, agro-tourism, home plants